KONVERSI LAHAN PERTANIAN KE NON-PERTANIAN : FUNGSI EKOLOGIS YANG TERABAIKAN - Handoyo, Eko (Forum Ilmu Sosial, 2010)
Indonesia had always been known as an agricultural country, because most of the population of Indonesia worked as a farmer. The agricultural sector is suspected to contribute to the Gross Domestic Product and has a strategic role in the Indonesian economy. Not only has that, done in a sustainable agriculture also had an invaluable ecological function. But the sustainability of agriculture is threatened due to the function of the rapidly growing industrial activities that encourage the transfer function of agricultural land. Some things such as government policy to privatize the development of industrial areas, policies that encourage large-scale residential development, investment and deregulation policies. The impact of policies over the functions of agricultural land, which is reduced which causes the vast fi elds of rice production decreased and in turn threaten the self-suffi ciency in food, rising unemployment, investment in irrigation abandoned, increasing non-productive agricultural land and the decline of wetland ecosystems and land. Governments seek to control the issuing of Act No. 41 of 2009, but seem less successful to overcome the desire of investors to converted agricultural land into industrial zones and housing. These laws have a mission to restore the ecological functions of agricultural land, diversifi cation of biodiversity, fl ood control, erosion and pollution prevention.Key words: conversion, agriculture, ecological